Asset encumbrance, bank funding and fragility - Toni Ahnert; Kartik Anand; Prasanna Gai; James Chapman (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
We propose a model of asset encumbrance by banks subject to rollover risk and study the consequences for fragility, funding costs, and prudential regulation. A bank's choice of encumbrance trades off the benefit of expanding profitable investment funded by cheap long-term secured debt against the cost of greater fragility due to unsecured debt runs. We derive several testable implications about privately optimal encumbrance ratios. Deposit insurance or wholesale funding guarantees induce excessive encumbrance and exacerbate fragility. We show how regulations such as explicit limits on encumbrance ratios and revenueneutral Pigouvian taxes can mitigate the risk-shifting incentives of banks.
Keywords: G01; G21; G28; 330; asset encumbrance; rollover risk; wholesale funding; fragility; runs; secured debt; unsecured debt; encumbrance limits; encumbrance surcharges